English language teaching practices at the tertiary level of Bangladesh: A public university alumni’s feedback - Md. Nazmul Haque (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
This study aims at exploring the problems and challenges faced by the students in the long English language teaching practices of the Department of English, Islamic University, Bangladesh, and the achievable modifications recommended by its alumni to ensure pragmatic English language teaching at the universities of Bangladesh. Both qualitative and quantitative or mixed-method approach was applied and a total of 21 alumni of various academic years from 2010 to 2022 (12 Years) of the Department of English at Islamic University, Bangladesh participated in the study. The findings of the study revealed that majority of the participants, after completing the graduation and post-graduation in English, failed to develop their English language skills at the advanced level due to the lack of some crucial issues, like particular course and test on specific skills (Speaking, Listening, Reading, and Writing), effective course design and teaching approach, learner-expected professional dedication of the English language teachers, practice and feedback session, and the use of technological devices in the language classroom and  language lab in the English language teaching practices. The study suggests that at least one particular course and test for each English language skills and more practice-oriented ELT courses should be added to the syllabus, and the language teachers should be more serious concerning course design, class activities, effective testing, feedback, use of technology-based classroom, blended learning approach, group discussion and implementation of specific as well as experience-based teaching approach to English language teaching.  DOI: 10.26905/enjourme.v7i1.8074